Thermal design of heat exchangers - Yeo, Hien Keong (2016)
In this project, it is aimed to create a calculation software program for engineering students and engineers to help them in the design and performance evaluation of two-phase plate heat exchangers. The program will be able to calculate the thermal and hydraulic performance of both single and two-phase plate heat exchangers. The single phase calculation program was developed previously by Aniz [12] and will be hyperlinked in the program main page. Due to limited availability of two-phase plate heat exchanger publications in the open literature, only certain fluids that are commonly used are incorporated in the program. The user will have the choice of changing the input parameters to suit the best design with respect to his or her requirements. Many of the design methods and heat transfer correlations for two-phase plate heat exchangers remain proprietary. Therefore, practising engineers and students do not have access to them. As a result, there is no generic form of heat transfer correlations available to the public. However, there are many correlations produced by individual researchers in the open literature which are only based on their experiments obtained under specified conditions and fluids. The software program is developed using Microsoft Visual C# 2010 which is in Windows Presentation Foundation (WPF). WPF is a graphical subsystem for representation user interfaces in Windows-based applications by Microsoft. iv It is capable of performing two-phase calculations such as evaporator rating and sizing, condenser rating and sizing. For rating, the user will need to input the required operating conditions and the program will calculate the total heat transfer and outlet temperature. For sizing, the user will need to input the required parameters for the new design and the program will calculate the required plate area and number of plates. The program has also been validated by comparing the results obtained through manual calculations with the results produced by the program. There will also be a tutorial in the software which aims to give the user a better understanding of the theory, design and assumptions used in the two-phase plate heat exchanger software.